Frugivory in Ameiva ameiva (Squamata: Teiidae) in a white-sand ecosystem of Central Amazonia, Brazil - Lozorio, Anderson; Cunha, Weslley (Herpetologia Brasileira, 2026)
Observations and natural history records of reptiles are crucial for understanding their ecology, particularly in the context of rapid habitat loss in the Amazon. Although the teiid lizard Ameiva ameiva is an active forager whose diet is well documented as being primarily arthropod‑based, records indicate dietary plasticity that includes the consumption of plant material. Here, we document the first observation of A. ameiva consuming the fruit umari (Poraqueiba sericea) in a white‑sand ecosystem (WSE) of the Central Amazon, Brazil. The lizard was observed actively feeding on the pulp of fallen fruits, suggesting that umari, which is rich in lipids and carotenoids, may serve as an alternative or supplemental energy source. This observation expands the known dietary breadth of A. ameiva and raises the possibility that this species may act as a short‑distance seed disperser, contributing to ecological interactions in understudied habitats such as WSEs.
Keywords: Animal-plant interaction; Dietary plasticity; Lizard; Natural history